Development of Teaching Material for Procedural Text through Nearpod Media for XI Grade Senior High School Students - Alif Wahyudi; Ansoriyah, Siti; Eriyani, Reni Nur (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2023)
This research aims to develop teaching materials for procedure text through Nearpod media. The research was prepared using the Research and Development (R&D) method with the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). Data collection was carried out through needs analysis interviews to teachers and distributing questionnaires to students through g-forms, curriculum analysis, teaching material analysis, material expert validation and media expert validation. In addition, the feasibility test was conducted to Indonesian language teachers and students of grade XI high school. Data analysis was carried out with qualitative and quantitative descriptive data analysis. The results of this study are in the form of teaching materials for procedural texts that can be accessed through Nearpod media. The feasibility of the product of teaching material for procedure text through Nearpod media for grade XI high school is included in the very good category. The results of the material expert assessment obtained an average score of 3.82. Furthermore, the media expert assessment obtained an average score of 4.5. The Indonesian language teacher assessment obtained an average score of 4.42. The student assessment obtained an average score of 4.28. Based on the results of this assessment, the teaching material for procedural text through Nearpod media for grade XI high school students is declared suitable for use in the learning process.